“TEMPE” REDUCES DNA DAMAGE IN RATS IRRADIATED WITH ULTRAVIOLET RAY - Maryam, Siti; Sudewa Djelantik, A. A. Gde; Agus Bagiada, I Nyoman; Mantik Astawa, Nyoman (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2011)
‘Tempe’ is a popular Javanese-Indonesian tradisional food made of fermentedsoyabean. This study aims to examine whether ‘tempe’, used as a strong anti-free,has the ability to decrease DNA damage induced by ultraviolet ray irirradiation inthe Wistar rats as indicated by the levels of urinary 8-hydroxy-2-deoxyguanosine.A Total of 24 Wistar rats, 2.5 to 3 mounths and 200 gr body weight, weredividing into 4 groups of equal size i.e. three treatment and one control groups.All rats were exposed to 5-hours daily UV ray sources of UV 15 watt Philip for 60days. Randomized post test only control group design was used in this study withindependent variables of 0, 1, 2 and 3 g ‘tempe’ per kilogram body weight per dayand independent variables of 8-hydroxy-2-deoxyguanosine urinary level as aDNA damage biomarker following an oxidative stress. Data were analyzed byusing one way ANOVA followed by Tukey HSD.The results of our study indicates that there is a decrease of DNA damageis manifested by progressive decrease of 8-hydroxy-2-deoxyguanosine level in thetreatment groups as compared to the control group. Statistically significantdecrease of 22.61 % and 25.62 % was shown with p > 0.05.From our analysed data is could be inferred that ‘tempe’ has the ability todecrease DNA damage caused by ultraviolet ray irradiation. Supplementation of2 g ‘tempe’ per kilogram body weight per day appeared to have the strongesteffect of decreasing DNA damage in Wistar rats.